Oxygen Activation Switch in the Copper Amine Oxidase of Escherichia coli - Gaule, Thembaninkosi G. (Biochemistry, 2018)
[Image: see text] Copper amine oxidases (CuAOs) are metalloenzymes that reduce molecular oxygen to hydrogen peroxide during catalytic turnover of primary amines. In addition to Cu(2+) in the active site, two peripheral calcium sites, ∼32 Å from the active site, have roles in Escherichia coli amine oxidase (ECAO). The buried Ca(2+) (Asp533, Leu534, Asp535, Asp678, and Ala679) is essential for full-length protein production, while the surface Ca(2+) (Glu573, Tyr667, Asp670, and Glu672) modulates biogenesis of the 2,4,5-trihydroxyphenylalanine quinone (TPQ) cofactor. The E573Q mutation at the surface site prevents calcium binding and TPQ biogenesis. However, TPQ biogenesis can be restored by a suppressor mutation (I342F) in the proposed oxygen delivery channel to the active site. While supporting TPQ biogenesis (∼60% WTECAO TPQ), I342F/E573Q has almost no amine oxidase activity (∼4.6% WTECAO activity). To understand how these long-range mutations have major effects on TPQ biogenesis and catalysis, we employed ultraviolet–visible spectroscopy, steady-state kinetics, inhibition assays, and X-ray crystallography. We show that the surface metal site controls the equilibrium (disproportionation) of the Cu(2+)-substrate reduced TPQ (TPQ(AMQ)) Cu(+)-TPQ semiquinone (TPQ(SQ)) couple. Removal of the calcium ion from this site by chelation or mutagenesis shifts the equilibrium to Cu(2+)-TPQ(AMQ) or destabilizes Cu(+)-TPQ(SQ). Crystal structure analysis shows that TPQ biogenesis is stalled at deprotonation in the Cu(2+)-tyrosinate state. Our findings support WTECAO using the inner sphere electron transfer mechanism for oxygen reduction during catalysis, and while a Cu(+)-tyrosyl radical intermediate is not essential for TPQ biogenesis, it is required for efficient biogenesis.